Algorithm Analysis of Massage Robot Technology: The Use of Techniques and Their Movements on the User's Bodyi - Fadhriz Qadrul Amien (Jurnal Mantik, 2022)
Technology is now very advanced, many people are competing to create a renewable innovation, one of which is in the field of robotics. Robot is a technology whose main focus is to help ease the work of humans or maybe help in other things that can increase the efficiency of a job and can make human work more comfortable because it is assisted by robots. This time it will focus on massage robots or massage robots, robots that perform reflexology or therapy to human limbs. This article will make an analysis of the robot's work, how it works, the results of the algorithm, a discussion of the results, as well as other supporting materials that will be presented. What needs to be emphasized is how this massage robot has instructions or algorithms that can be executed so that he can complete the work, there are several massage robots that have continuous repetition, so that they end up being inefficient in their work, for that it is necessary to pay attention to the algorithm on the massage robot